Legal Reconstruction of the Fragmentation of the Professional Advocate Organization and its Implications for Law Enforcement - Jutek Bongso; Hernawati RAS; Eni Dasuki Suhardini (Law Development Journal, 2026)
The legal profession constitutes one of the key components of law enforcement with a strategic role in upholding the rule of law, protecting human rights, and ensuring access to justice. The position of advocates as a free and independent profession presupposes the existence of a professional organization capable of structuring authority, maintaining professional competency standards, and enforcing ethical rules consistently. However, in practice, the regulation of advocate organizations in Indonesia under Law No. 18 of 2003 on Advocates has resulted in prolonged organizational fragmentation. Such fragmentation has generated uncertainty in the governance of the legal profession and has adversely affected the quality of law enforcement and legal certainty within the judicial system. This research aims to analyze the urgency of reconstructing the regulation of advocate organizations, to identify the factors underlying organizational fragmentation along with its implications, and to formulate an ideal model for reconstructing the advocate organizational system in Indonesia. The findings indicate that organizational fragmentation among advocates is a consequence of a regulatory design that fails to provide clear mechanisms for managing authority, organizational legitimacy, and conflict resolution. Internal factors, including leadership legitimacy crises and inconsistencies in the exercise of professional authority, intersect with external factors such as normative weaknesses, judicial interpretation, and evolving administrative practices. These conditions result in divergent professional standards, weakened systemic cohesion, and diminished legal certainty for the advocate profession. Based on these findings, this research proposes a reconstruction model through a hybrid single bar system, which centralizes fundamental professional authority within a single national structure while recognizing organizational plurality within clearly defined limits. This model is intended to safeguard professional independence, ensure consistency of professional standards, and strengthen the role of advocates as law enforcement actors. Accordingly, the study recommends either a revision of Law No. 18 of 2003 on Advocates or the enactment of implementing regulations as the normative foundation for the proposed reconstruction.